Pengaruh Penggunaan Elastic Lumbal Corset Terhadap Penurunan Derajat Nyeri Pinggang Pada Buruh Tani Di Desa Tinawas Nogosari Boyolali - Cica Tri Mandasari Ningsih; Dwi Setyawan (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Back Pain, Pain, Lumbar Elastic Corset. The research was purposed to determine the effect of the use of elastic lumbar corset against degradation of low back pain in farm workers. The low back pain is pain that occurs in the area of the lower back and can spread to the foot, especially the back and sides outside. Giving elastic lumbar corset is one way to deal with complaints of back pain is often experienced farm workers. The subjects included 20 farm laborers in the village Tinawas Nogosari Boyolali. To analyze the data, it use quasi experiment methode with approaches one group pre and post test design. The statistical analysis using non-parametric tests of hypotheses for subjects <30 using Wilcoxon test. The Treatment in this research that the whole subject is applied elastic lumbar corset for 2 weeks. The result showed that the VAS values of different test results using Wilcoxon test, the pre and post test result p = 0.000 (<0.05), which means it can be concluded there is peberbedaan or significant influence between before and after the use of elastic corset. So, the hypothesis proposed in this research was accepted. In conclusion, it can be said that pain management waist on a farm laborer using elastic lumbar corset can reduce pain she felt every day on a farm laborer in the village Tinawas Nogosari Boyolali.